2020
DOI: 10.1103/physrevb.102.125418
|View full text |Cite
|
Sign up to set email alerts
|

Growth of germanium-silver surface alloys followed by in situ scanning tunneling microscopy: Absence of germanene formation

Abstract: Theoretical studies have shown that new physical properties such as tunable gap opening or quantum spin Hall effect could be expected from group IV graphene analogues (silicene, germanene, stanene). While there have been numerous studies of growth of such Si, Ge, Sn monolayers, the demonstration of their hexagonal organization has been often based on postgrowth characterization and their analogy to graphene has remained controversial. Our realtime scanning tunneling microscopy (STM) observation during Ge depos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 36 publications
6
24
1
Order By: Relevance
“…2 a. According to similar reports of this superstructure, mainly obtained from LEED and STM measurements, the formation can be attributed to a surface alloy 22 , 24 28 . Its particular structure will be discussed in “ XPD ”.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…2 a. According to similar reports of this superstructure, mainly obtained from LEED and STM measurements, the formation can be attributed to a surface alloy 22 , 24 28 . Its particular structure will be discussed in “ XPD ”.…”
Section: Resultssupporting
confidence: 68%
“…The first experimental study on thin films of epitaxially grown germanium on Ag(111) mainly reported a surface alloy at a coverage of , arranged in a reconstruction 23 , 24 . However, this alloy phase at a layer thickness of germanium is still controversially discussed to form reconstructions of a 25 28 , a 29 , a with a Moiré pattern of 30 , or a rectangular 31 . It was also considered as a striped phase (SP) due to tensile strains of the uppermost layer 32 with a long-range order of 26 .…”
Section: Introductionmentioning
confidence: 99%
“…This reconstruction was further recognized as a c�√3 × 7� reconstruction and a model of Ge tetramers on top of a Ag(111) plane was proposed for its structure, based on scanning tunneling microscopy (STM) [6]. In contradiction with this model, from real-time STM observations of the growth, we have recently proposed that this latter structure is also a surface alloy with a coverage of 0.6 ± 0.1 ML [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, several issues have recently been raised by different authors regarding the successful synthesis of pure layers of these bidimensional materials, especially when they are grown on metal substrates. [12][13][14][15][16][17][18][19] Therefore, further research is necessary to throw light on this present controversy.Among this vast portfolio of 2D materials, antimonene has received a strong amount of interest due to its attractive properties. It has been theoretically predicted to feature a tunable semiconducting band gap, [20,21] a relatively high carrier mobility [22] or quantum spin Hall effect.…”
mentioning
confidence: 99%
“…However, several issues have recently been raised by different authors regarding the successful synthesis of pure layers of these bidimensional materials, especially when they are grown on metal substrates. [12][13][14][15][16][17][18][19] Therefore, further research is necessary to throw light on this present controversy.…”
mentioning
confidence: 99%